Удосконалення технології виробництва соковмісних напоїв з використанням дикорослої сировини - Матко, Світлана Василівна; Левківська (Музика), Тетяна Миколаївна; Мельник (Ткачук), Наталія Андріївна (My University, 2020)
На основі аналізу літературних джерел обґрунтовано доцільність використання саме нетрадиційної дикорослої сировини (глід) в технології виробництва соковмісних напоїв. Встановлено кінетичні закономірності екстрагування РСР при температурах 20, 30, 40, 50°С. Вивчено вплив НВЧ оброблення на величину вилучення РСР з плодів глоду. 3. Досліджено вміст аскорбінової кислоти, екстрактивних речовин та рН отриманих екстрактів, які дають змогу конструювати рецептури нових продуктів і керувати технологічним процесом одержання соковмісних напоїв. Wild raw materials are a valuable source of biologically active substances such as bioflavonoids, ascorbic acid, pectin and minerals. Hawthorn fruit are rich on pectin and ascorbic acid, so usage of hawthorn in food technology is relevant. This work was devoted to studying the extraction process of complex of biologically active substances of wild hawthorn fruit and using the obtained extract in juice drinks technology. The extraction process of the crushed hawthorn mass was carried out in water at a hydraulic modulus 1:1.5…1:2 with additional microwave treatment and without it. The temperature was changed from 20°C to 50°C. As a result, the kinetic extraction regularities of soluble solids at temperatures of 20°C, 30°C, 40°C, 50°C were established. It was found that microwave radiation pre-treatment of hawthorn fruit allowed to extract more dry matter (an average of 15% compared to samples without additional processing). The extracts obtained at different extraction temperatures of 20—50°C were investigated for the content of ascorbic acid, extractives and pH. It was found that the implementation of extraction at 40—50°C promoted better ascorbic acid saving and the extractives transition іnto the extract up to 30% of the raw material, while the pH level was less than 3.0. It can be concluded that the highest BAS content can be obtained by extraction of microwave pre-treated hawthorn fruit and subsequent extraction in water at a hydraulic modulus of 1:1.5…1:2 at a temperature of 40—50°C. This extracts were blended with fruit juices. Such drinks had a high BAS content, harmonious taste and flavor.
Keywords: кафедра технології консервування; кафедра процесів і апаратів харчових виробництв; соковмісні напої; дикорослак сировина; глід; екстрагування; технологічні параметри; technological parameters; juice drinks; wild-breed raw materials; hawthorn; extraction